5′-UTR of malS increases the invasive capacity of Salmonella enterica serovar Typhi by influencing the expression of bax. (June 2015) - Gong, Mingyu; Xu, Shungao; Jin, Yue; Zhang, Ying; Dadzie, Isaac; Zhang, Xiaolei; Wang, Zhexin; Zhu, Yunxia; Ni, Bin; Sheng, Xiumei; Huang, Xinxiang
ABSTRACT : Aim: An RNA-seq analysis recently identified a 236-nucleotide transcript upstream from malS in Salmonella enterica serovar Typhi. Here, we investigated its molecular characteristics and function.Materials & methods: RACE and northern blotting were used to determine the molecular characteristics of the sequence, and mutagenesis, microarray, immunoblotting and an invasion assay were used to investigate the functions of the transcript.Results: The transcript was identified as the malS 5′-untranslated region (UTR), which could influence the expression of the flagellar and SPI-1 genes and the invasion of HeLa cells by S . Typhi. Deletion of bax increased the expression of the invasion genes and the invasive capacity of S . Typhi, whereas the expression of the malS 5′-UTR reduced the expression of bax .Conclusion: The malS 5′-UTR reduces the expression of bax and increases the invasive capacity of S . Typhi.